MANIPULASI IDENTITAS DIRI DI MEDIA SOSIAL (Analisis Isi Kualitatif Pada Film “The Tinder Swindler”) - Vianty, Marda; Umarella, Farid Hamid (Universitas Mercu Buana, 2024)
Social media exists as a means to communicate with other people. Socializing, working, dating, and sharing life stories on social media are daily activities carried out by people from all over the world. As a result of freedom of communication, various crimes arise on social media.This research focuses on the elaboration of the act of identity manipulation, which describes the acts of self-identity manipulation on social media contained in the documentary film “The Tinder Swindler” so that it can be seen how this phenomenon occurs in real life.The research method used is a qualitative research method with a content analysis approach which aims to analyze the manipulation actions used, so that it can be known how fraud perpetrators manipulate other people.The results obtained from this study are 45 scenes that are in accordance with the categorization in the analysis. Identity manipulation was found related to name, job, appearance, social environment, and photos & videos on social media. With the elaboration of self-identity manipulation in this research, it is hoped that the public will be more aware of other people they meet on social media in order to avoid similar scams, as happened in The Tinder Swindler film.